The constraints to the economic development in the former socialist EU countries from the Central and Eastern Europe - Vasile Dinu (Amfiteatru Economic)
In the last 25 years, most Central and Eastern European states have become detached from the centralized economy system thus demonstrating the reliability of the market economy. The unequivocal effect of the free market, with ups and downs, forces researchers to undertake increasingly complex economic analysis and further the profile of the new economy. With the accession of a number of countries from this region to the European Union there were some constraints and limitations in adopting the European acquis, whose knowledge and solution involves the use of specific policies and tools. We consider the problems related to the resolution of economic, social and technological discrepancies and gaps, of mitigating the negative impact of unfavourable demographic trends, of elucidating the role of the state amid the erosion of its duties due to the process of integration and globalization, of increasing pressure interdependencies interstate and others.